An Analysis of Travel Demand in Japan's Intercity Market Empirical Estimation and Policy Simulation. (1st January 2014) - Fu, Xiaowen; Oum, Tae; Yan, Jia
This study estimates a travel demand model in Japan's intercity market with aggregate OD data. The estimated model is used to estimate the effects of introducing super high-speed-rail (HSR), and alternative levels of CO2 emission taxation on the demands for airline and HSR modes. It is found that: (a) there is clear product differentiation between air and rail travel; (b) Japanese consumers are sensitive to travel time and frequency; (c) the proposed Tokyo–Osaka HSR services would drive airlines out of the route while stimulating substantial new traffic; and (d) CO2 taxation would have a moderate impact on modal shift.